Réponses

2013-09-25T17:35:47+02:00
3(x-1)+2(x+3)=0
3 * x + 3 * (-1) + 2 * x + 2 * 3 = 0
3x + (-3) + 2x + 6 = 0
5x + 3 = 0
5x = 0 - 3
5x = -3
x = -0,6

-5(x+2)+3(x-3)=7
-5 * x + (-5) * 2 + 3 * x + 3 * (-3)=7
-5x + (-10) + 3x + (-6)=7
-2x + (-16)=7
-2x = 7 + 16
-2x = 23
= x = -11,5

4(-x+1)-2(3x-5)=0
4 * (-x) + 4 * 1 + (-2) * 3x + (-2) * (-5)=0
-4x + 4 + (-6x) + 10=0
-10x + 14=0
-10x = 0 - 14
-10x = -14
x = 1,4

7(2x-6)-4(5x-8)=-5x
7 * 2x + 7 * (-6) - 4 * 5x + (-4) * (-8) = -5x
14x + (-42) - 20x + 32 = -5x
34x + (-10) = -5x
-10 = -5x - 34x
-10 = -39x
x = -0,25
pour la dernière équation, je ne suis pas sur.